Current and emerging treatment approaches for hormone receptor-positive/human epidermal growth factor receptor 2-negative metastatic breast cancer - Jhaveri, Komal; Marmé, Frederik (Cancer treatment reviews, 2024)
In the past decade, significant progress was made in treating hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) metastatic breast cancer (mBC), but many clinical questions remain. Cyclin-dependent kinase 4/6 inhibitors are now widely used in combination with endocrine therapy (ET) as standard of care, having demonstrated significant progression-free survival versus ET, and also significant overall survival benefits in the metastatic setting. Inhibition of the PI3K/AKT/mTOR intracellular signaling pathway coupled with ET typically follows first-line therapies. Novel endocrine options including oral selective estrogen receptor down-regulators (SERDs) are in late phases of development, with elacestrant being the first oral SERD to be approved for ESR1-mutant mBC. However, endocrine-refractory disease is inevitable in most patients and represents an area of unmet need, with current recommended options offering poor efficacy, undesirable toxicity, and reduced quality of life. Breakthrough advances in the metastatic setting came via the development of antibody-drug conjugates, which have the advantage of delivering cytotoxic payloads to tumor cells with higher tumor selectivity. Trastuzumab deruxtecan offers a novel therapeutic option for patients with HR+/HER2-low mBC and sacituzumab govitecan is a novel therapeutic option for patients with HR+/HER2− mBC, including those with unmet treatment need in the later-line endocrine-refractory setting. Data gaps still exist regarding optimal sequencing of these novel agents; additional studies into mechanisms of resistance in the metastatic setting would provide further insights. Herein, we describe the current treatment options for HR+/HER2− mBC, including the latest practice-impacting data, and provide commentary on future directions.
Online verfügbar: 9. Dezember 2023, Artikelversion: 11. Januar 2024
Gesehen am 13.06.2024